Natural Convection Heat Transfer of the Horizontal Rod-Bundle in a Semi-closed Rectangular Cavity - Mao, Xi-dao; Xia, Hong (Frontiers in Energy Research, 2020)
During the refueling of PWR, the spent fuel assemblies are transferred from the reactor building to the fuel building through an underwater tube. The heat transfer characteristics of the spent fuel assembly in the top-corner area of the carrier with poor heat transfer conditions is important for the safety design. Experiments were carried out and single phase natural convection and pool boiling heat transfer coefficients of the three fuel rods in the top-corner area of the carrier under different heat flux was measured and obtained. The new correlations were presented. The results can provide a reference for evaluating the thermal safety state and the maximum surface temperature of the fuel assembly during the transportation process in future engineering applications.